2020
DOI: 10.1016/j.hlpt.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response to crisis: Health system lessons from the active period of COVID-19

Abstract: Highlights COVID-19 has become the epitome of complex health problems where evidence-based medicine should be completed with other scientific approaches to facilitate informed planning. Rapid response prioritisation should incorporate systems thinking and healthcare ecosystem approaches as well as new methods to collect expert knowledge using new technologies. Digital conferencing has proven feasible and usable to get a quick and transparent appraisal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 33 publications
0
29
0
6
Order By: Relevance
“…Major challenges included the initial provision of PPEs for professionals and users as well as a rapid technological predisposition for a broader use of remote devices. These issues were similar for the general healthcare sector, especially in countries which experienced an explosive acceleration of the pandemic, such as Italy [ 2 , 13 , 14 ], although research from Catalonia (Spain), which has been facing a situation similar to Italy, showed an exponential increase in teleconsultations from the March 2020 [33] . In spite of these challenges, regional MHDs complied quickly with the operative recommendations, and monitoring indicators were mostly achieved after one month from their delivery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Major challenges included the initial provision of PPEs for professionals and users as well as a rapid technological predisposition for a broader use of remote devices. These issues were similar for the general healthcare sector, especially in countries which experienced an explosive acceleration of the pandemic, such as Italy [ 2 , 13 , 14 ], although research from Catalonia (Spain), which has been facing a situation similar to Italy, showed an exponential increase in teleconsultations from the March 2020 [33] . In spite of these challenges, regional MHDs complied quickly with the operative recommendations, and monitoring indicators were mostly achieved after one month from their delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In FVG, however, psychiatric patients, even with severe conditions, had the possibility of being discharged discharged from hospital and being hosted in outpatient services. This could have led to choose CMHCs for managing patients with psychopathological difficulties, and decrease pressure on hospitals, more engaged in crisis response [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations